Two-reactant-form sheet-like tissue adhesion reinforcing material
By fixing the powder of the 2-reaction dosage-form adhesive on the biologically decomposed porous substrate, and using anhydrous ethanol dispersion technology, the problems of infection risk and operation complexity in the prior art are solved, and safe and simple biological tissue bonding and strengthening effects are achieved.
Patent Information
- Application Number
- CN202510087610.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-14
- Filing Date
- 2019-12-09
- Publication Date
- 2025-04-18
AI Technical Summary
Existing sheet-like tissue bonding reinforcement materials have risk of infection and complexity in the use of fibrinogen or thrombin, and it is difficult to achieve both safety and simplicity.
The powder of the 2-reaction dosage-form adhesive is dispersed with anhydrous ethanol and fixed on the biologically decomposed porous substrate, avoiding the use of fibrinogen and thrombin to achieve the effect of bonding and strengthening.
It achieves safe, simple bonding and strengthening of biological tissues, avoids the risk of infection, and maintains the reactivity and adhesiveness of the adhesive.
Smart Images

Figure CN119838046A_ABST
Abstract
Description
[0001] This application is a divisional application with an international filing date of December 9, 2019, and an invention name of “2-reaction formulation sheet-like tissue bonding reinforcement material” and an application number of 201980082918.6. Technical Field
[0002] The present invention relates to a biodegradable sheet-shaped adhesive reinforcement material, which can be bonded to a biological tissue to reinforce or cover the bonded part, and can be used as a hemostatic material, an air leakage prevention material, an adhesion prevention material, a suture reinforcement material, an adhesive sheet, etc. In particular, it relates to a sheet-shaped tissue adhesive reinforcement material in which a two-reactive agent type adhesive powder is fixed on a biodegradable porous substrate. Background Art
[0003] As representative sheet-like tissue adhesive reinforcement materials available on the market, there are: fibrinogen preparations, preparations using polysaccharides, and preparations using aliphatic polymers. "TACHOSIL" (registered trademark, CSL Behring Co., Ltd.), which is a fibrinogen preparation, is a preparation in which fibrinogen and thrombin (Thrombin) from blood are attached to a sheet-like collagen sponge (collagen sponge). In order to achieve this attachment, a solution of fibrinogen and thrombin, etc. is sprayed onto the collagen sponge and then dried (Patent Documents 2 to 3). On the other hand, as commercially available preparations that do not contain adhesive components and use porous sheets of polysaccharides or aliphatic polymers, "Surge Cell" (registered trademark, Johnson & Johnson Co., Ltd.: oxidized cellulose cloth) and "NEOVEIL" (registered trademark, Gunze Co., Ltd.: non-woven fabric of polyglycolic acid) are known. In addition, an absorbent local hemostatic material is commercially available (trade name "Integran", manufactured by Koken Co., Ltd. and sold by Nippon Zanki Pharmaceutical Co., Ltd.) obtained by spinning calf dermis-derived atelocollagen into cotton fibers and chemically cross-linking them with a polyepoxide.
[0004] As a tissue adhesive or tissue reinforcement material that does not use biological raw materials, there is a two-reaction formulation material including a mixed powder of aldehyde-deoxyglucan and modified poly-L-lysine as proposed by the present applicant (Patent Document 1). This tissue adhesive reinforcement material is sprayed onto the application part in a powder state, and then gelled by spraying physiological saline, so that it is adhered to the application part in a sheet form. The hemostatic effect and the anti-leakage effect on the lung resection surface have been confirmed by animal experiments (for example, Non-Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. WO2008 / 066182 (Japanese Patent No. 4571693)
[0008] Patent document 2: Japanese Patent Publication No. 61-034830
[0009] Patent Document 3: International Publication No. WO2012 / 029971
[0010] Patent document 4: Japanese Patent Laid-Open No. 2017-192560
[0011] Non-patent literature
[0012] Non-patent literature 1: Development of new biodegradable hydrogel glue for preventing alveolar air leakage, J. Thoracic and Cardiovascular Surgery, 134(5): 1241-8 (2007 Nov).
[0013] However, fibrinogen preparations represented by "TACHOSIL" are preparations made from blood components, so there is a risk of infection from the blood. "Surge Cell", which does not use blood components as raw materials, uses the patient's own coagulation ability to absorb blood into the porous sheet of Surge Cell to form a blood clot, thereby achieving a tissue reinforcement effect. Therefore, after attaching it to the hemostasis site, it takes several minutes to press until a blood clot is formed. In addition, in order to enhance the adhesion of the foot to biological tissues, it is recommended to use "NEOVEIL", a porous sheet of aliphatic polymers, together with fibrinogen preparations. Therefore, it is difficult to say that existing sheet-like tissue reinforcement materials have both safety and simplicity. Summary of the invention
[0014] The present invention has been made to solve such a problem, and an object of the present invention is to achieve the effects of adhesion and reinforcement of tissues without using either fibrinogen or blood coagulation ability derived from the patient's biological body in a sheet-like tissue adhesion and reinforcement material.
[0015] The medical two-reactive agent adhesive described in WO2008 / 066182 (Patent Document 1) is applied in a powder state to an incision, wound, etc. of a biological tissue. When physiological saline is added, the two reaction components react with each other, thereby crosslinking or polymerizing, and the properties change from powder to hydrogel. The hydrogel has adhesion to biological tissues and has the characteristic of hindering the permeation of liquids and gases by the hydrogel monomer. The hemostatic effect as an effect of strengthening tissue adhesion and the anti-leakage effect on the lung resection surface have been confirmed through animal experiments. In addition, the powder of the medical two-reactive agent adhesive is a porous body of random shape obtained by drying and pulverizing an aqueous solution by freeze drying, etc., and the average particle size is 10 to 150 μm.
[0016] The inventors of the present application have made various attempts to obtain sheet-shaped tissue adhesive reinforcement materials using the above-mentioned medical two-reactive agent adhesive in the form of powder. However, the medical two-reactive agent adhesive is insoluble in solvents other than water. In addition, when dissolved in water, the aldehyde group of the aldehyde-formylated glucan (glucan) reacts with the amino group of the modified poly-L-lysine, resulting in a decrease in the adhesion of the aqueous gel to the biological tissue in a state where the reaction is almost completed. Therefore, it is not possible to attach to a porous substrate sheet using the same method as the method for attaching fibrinogen and thrombin, etc.
[0017] Even if the powder of aldehyde-deoxyglucan and the powder of modified poly-L-lysine are dissolved separately in water, for example, the aqueous solution of aldehyde-deoxyglucan is sprayed on the substrate sheet and dried, and thereafter, if the aqueous solution of modified poly-L-lysine is sprayed, the reaction between the aldehyde group of aldehyde-deoxyglucan and the amino group of modified poly-L-lysine still proceeds. It is also conceivable to apply the powder in fine dots or stripes, but the process is very complicated and not practical.
[0018] On the other hand, it is also considered that the powder of the above-mentioned medical two-reactive agent type adhesive is encapsulated in a capsule, or an adhesive (Binder) is used to attach it to a porous substrate. However, if a capsule or an adhesive is used, it is possible to prevent the reaction material component from contacting water quickly, causing the curing (gelation) to be delayed or incomplete. In addition, the process for attaching it to a porous substrate may become complicated.
[0019] The inventors of the present application have studied and found that it is possible to obtain a sheet-shaped tissue adhesive reinforcement material using the above-mentioned two-reactive agent adhesive for medical use by a simple method such as anhydrous ethanol. That is, the powder of the two-reactive agent adhesive for medical use is dispersed in anhydrous ethanol, etc., and then added to a biodegradable porous sheet such as a collagen sponge sheet by spraying or dipping, and then dried and the ethanol is removed. As a result, unexpectedly, the powder of the two-reactive agent adhesive for medical use is fixed on the biodegradable porous sheet, and even if vibration or some impact is applied to the porous sheet, the powder of the two-reactive agent adhesive for medical use will not fall off.
[0020] In addition, the sheet-shaped tissue adhesive reinforcement material thus obtained has the same reactivity and adhesiveness as the powder of the medical two-reactive agent adhesive, that is, when attached to the incision or wound site of the biological tissue and appropriately sprayed with physiological saline, it quickly absorbs water and solidifies (gels), and firmly adheres to the biological tissue.
[0021] The solidified hydrogel also has adhesion to a biodegradable porous sheet (hereinafter, appropriately referred to as "substrate sheet") having a hydrophilic group on the surface, and when the tissue bonding reinforcing material is attached to the biological tissue, it also has the function of bonding the biological tissue to the substrate sheet. Therefore, not only can the biological tissues be bonded to each other by the sheet-like tissue bonding reinforcing material, but it can also be attached to the wound site of the biological tissue, etc., to perform the function of protecting and reinforcing the site. For example, if it is attached to the wound site of the biological organ, it can firmly cover / close the wound site before the healing is completed, and perform the reinforcing function of preventing deformation and crack generation caused by external forces, etc.
[0022] That is, sheet-like tissue bonding strengthening material of the present invention, in addition to the tissue strengthening effect based on the solidified hydrogel itself and the effect of covering / sealing, also has the tissue strengthening effect based on the substrate sheet, thus can realize further tissue strengthening effect, and realize the strong sealing effect that physically hinders liquid and gas from passing through.Particularly, can carry out compression hemostasis to the bleeding position of ejection / exudation, expand convenience.In addition, in the present application, "tissue bonding strengthening" is used with the meaning of comprising hemostasis, air leakage prevention, preventing tissue adhesion, suturing strengthening and the protection of trauma surface, and the obtained effect comprises: blocking the effect of gas and liquid passing through from both sides inside and outside of biological tissue, hindering the effect of contact of biological tissue with other biological tissues or solid matter and keeping the effect of biological tissue surface.
[0023] In the sheet-like tissue bonding reinforcing material of the present invention, the gelation of the two-reactant type adhesive powder for achieving bonding is initiated by the addition of water. The water that initiates gelation has nothing to do with the form / type. The water as the gelation initiator can be: water on the biological tissue that forms body fluids and blood, physiological saline or glucose solution.
[0024] Effects of the Invention
[0025] It can eliminate or reduce the risk of infection and has excellent operability and tissue strengthening effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a series of photographs showing the state when a two-reactant type adhesive powder (LYDEX (registered trademark)) was added to ethanol having various water contents and stirred (Example 2).
[0027] Figure 2 This is a set of diagrams for illustrating the procedure of an air leakage test (Example 3) using rabbit lungs.
[0028] Figure 3 The photographs are taken from a vertically inclined direction and show two types of mesh sheets (2.5×5 cm) obtained by spinning and knitting poly-L-lactic acid (PLLA) in a folded state.
[0029] Figure 4 It means in Figure 3 A set of photographs showing the situation when the adhesive resin layer is formed on the side with finer pores (mesh openings) in the mesh sheet ("PLLA mesh density") (Example 4-1).
[0030] Figure 5 It means in Figure 3 A set of photographs showing the situation when the adhesive resin layer is formed on the coarse side (“coarse PLLA mesh”) of the mesh sheet (Example 4-2).
[0031] Figure 6 This is a schematic diagram showing the outline of an in vitro adhesive strength evaluation test (Example 6) for the adhesive sheet of Example 4-1.
[0032] Figure 7 These are photographs showing the state of the adhesive strength evaluation test (Example 6).
[0033] Figure 8 This is a graph showing the results of the adhesive strength evaluation test (Example 6).
[0034] Fig. 9This is a right side view of a powder spraying device (spray gun; Japanese Patent Application No. 2017-222915) for applying a two-reactant type adhesive (LYDEX), with the right side shell portion removed.
[0035] Fig.10 The photographs collectively show an adhesive sheet using a cotton fibrous collagen sheet as a base sheet (Example 7) and an adhesive sheet using hydroxypropylcellulose (HPC) applied to the same base sheet to form 20% of the resin powder (Example 8).
[0036] Fig.11 This is a photograph showing a state in which the adhesive sheet of Example 7 is temporarily rolled up into a roll and then opened and stretched.
[0037] Fig.12 The adhesive sheet of Example 8 is Fig.11 Same photo.
[0038] Fig.13 This is a set of photographs showing the state at each stage of forming the adhesive sheet in Reference Example 1 using anhydrous ethanol.
[0039] Fig.14 It is expressed in two magnifications (×100 and ×400) Fig.13 The EtOH impregnated product and the EtOH partially dried product shown in the middle section ("4") and Fig.13 The lower section shows an enlarged photograph of the surface after drying.
[0040] Fig.15 About Fig.13 The lower panel shows an enlarged photograph of a cut surface of the dried sheet.
[0041] Fig.16 The following are the results of the steps of Reference Example 2 using non-aqueous acetone. Fig.13 The same set of photos.
[0042] Fig.17 It is expressed in two magnifications (×100 and ×400) Fig.16 The acetone impregnated product and the acetone partially dried product shown in the middle section ("4") of Fig.13 The lower section shows an enlarged photograph of the surface after drying.
[0043] Fig.18 The left and right photographs show side by side a powder of a two-component adhesive after being dispersed in non-aqueous acetone and then completely dried (left) and a powder of an original two-component adhesive (right).
[0044] Fig.19This is a set of photographs showing the conditions at various stages of Reference Example 3 using 2% aqueous acetone. From the left, the dispersion in the dish, the condition immediately after the dispersion is applied to the substrate sheet, the adhesive sheet after drying, and the condition of the adhesive sheet being picked up by pinching with tweezers are shown.
[0045] Fig. 20 About Fig.19 The following is a microscopic photograph of the surface of the adhesive sheet after drying.
[0046] Fig.21 This is a set of photographs showing the conditions at various stages of Reference Example 4 using a non-reactive similar mixed powder.
[0047] Fig. 22 This is a set of photographs showing the conditions at various stages of Reference Example 5 in which only modified polylysine (second reactant; SAPL) was used instead of a two-reactant type adhesive. DETAILED DESCRIPTION
[0048] The sheet-like tissue adhesive reinforcement material of the present invention (hereinafter, also appropriately referred to as "adhesive sheet") is a material obtained by fixing the powder of a two-reactive agent type adhesive for medical use to a biodegradable porous interconnecting sheet (substrate sheet), and is a material in which no third material such as an adhesive, a binder, or a covering material is inserted during the fixing. The fixing here means that even when the sheet-like tissue adhesive reinforcement material is bent, all or most of the powder of the two-reactive agent type adhesive is at least bonded to a degree that it does not fall off. In a preferred embodiment, as described in detail later, it is believed that the fixing is produced by partially dissolving a part of the powder of the two-reactive agent type adhesive, especially the surface layer of the powder of the modified poly-L-lysine.
[0049] The two-reaction type adhesive herein, particularly the two-reaction type adhesive in the form of a mixed powder described in WO2008 / 066182 (Patent Document 1), reacts in the presence of water to form a hydrogel. That is, it includes a mixed powder obtained by mixing a first reactant composed of a powder of aldehyde-modified glucan (aldehyde-modified polysaccharide, particularly water-soluble aldehyde-modified polysaccharide) having a weight average molecular weight of 1000 to 200,000 and a second reactant composed of a powder (B1) of poly-L-lysine to which anhydride is added (partially carboxylated) obtained by adding carboxylic anhydride to poly-L-lysine (A) having a weight average molecular weight of 1000 to 20,000 so that the molar ratio of aldehyde group / amino group is 0.9 to 3.5, wherein the aldehyde-modified glucan is obtained by oxidizing a polysaccharide such as water-soluble or water-dispersible glucan (polymer of D-glucose) with periodic acid or periodate and introducing 0.1 to 1.0 aldehyde group into each anhydroglucose unit. In a preferred embodiment, the glucan herein is α-glucan, such as dextran or dextrin. The glucan (polysaccharide) may be glycosaminoglycan such as hyaluronic acid, guar gum, locust bean gum, carrageenan, hydroxypropyl methylcellulose, hydroxypropyl cellulosic, or the like.
[0050] The powder of aldehyde-deoxyglucan and the powder of poly-L-lysine added with anhydride (B1) before being fixed on the substrate sheet are both porous bodies with random (irregular) shapes (shapes far from spheres) and an average particle size of 10 to 150 μm. The porous bodies with random shapes are obtained by drying aqueous solutions of aldehyde-deoxyglucan and poly-L-lysine added with anhydride by freeze drying or the like, and then crushing them with a high-speed rotating blade mill or the like, or powders equivalent thereto. The powder of aldehyde-deoxyglucan and the powder of poly-L-lysine added with anhydride (B1) thus obtained are mixed in a prescribed ratio to obtain a mixed powder as a two-reactant type adhesive. The mixed powder is preferably stored in a sealed container or the like in a manner that maintains a moisture content of less than 2.0%, particularly less than 1.0%.
[0051] Preferably, the two-reactant adhesive is a mixed powder comprising a first reactant consisting of a powder of aldehyde-modified dextran having a weight average molecular weight of 1,000 to 200,000 and a second reactant consisting of a powder of partially carboxylated poly-L-lysine having a residual amino group rate of 70 to 93% by reacting succinic anhydride or glutaric anhydride with poly-L-lysine having a weight average molecular weight of 1,000 to 20,000, in such a manner that the molar ratio of aldehyde group to amino group is 0.9 to 2.0, wherein the aldehyde-modified dextran is obtained by oxidizing dextran or dextrin with periodic acid or periodate to introduce 0.2 to 0.5 aldehyde groups per anhydroglucose unit (monosaccharide unit). In addition, preferably, the water content is 2.0% or less. The two-reaction adhesive for medical use can be adjusted and set in the range of 2 to 3 days to 4 weeks or more by changing the amount of aldehyde groups introduced in the aldehyded dextran within the range of 0.2 to 0.4 per anhydroglucose unit (monosaccharide unit).
[0052] In a preferred embodiment, the average particle size of the powder of aldehyded dextran and the powder of poly-L-lysine to which anhydride is added is in the order of more preferred ranges from (1) to (7) below. (1) 1 to 500 μm, (2) 5 to 350 μm, (3) 10 to 250 μm, (4) 10 to 150 μm, (5) 15 to 120 μm, (6) 20 to 100 μm, (7) 20 to 80 μm. That is, although 10 to 150 μm is referred to as a particularly preferred range, 15 to 120 μm and the like are more preferred ranges. Here, the average particle size is obtained by using an image analysis program (for example, the image analysis particle size distribution measurement software "MacView" produced by Mountech Co., Ltd. can be used) etc., to obtain the biaxial average diameter (simple average x of the major axis length and the minor axis length) of each particle based on the image obtained by a stereoscopic microscope and to perform length average (∑x 2 / ∑x). The average aspect ratio (major axis length / minor axis length) of the powder is, for example, 1.3 to 3.0, particularly 1.5 to 2.0. In addition, the average particle size can be more easily measured using, for example, a laser diffraction particle size distribution measuring device SALD-2200 (laser diffraction / scattering method, using a batch cell) and an analysis program (WingSALD II-2200for Japanese software) manufactured by Shimadzu Corporation, and a result substantially the same as the above-mentioned image analysis can be obtained.
[0053] Typically, in the distribution of the average diameters of both axes, the powder of aldehyde-deoxyglucan and the powder of poly-L-lysine to which the acid anhydride is added, which form the two-reactive agent type adhesive, contain 90% or more in the range of 10 to 150 μm, and contain 80% or more in the range of 20 to 100 μm. In addition, the average particle size of the powder of aldehyde-deoxyglucan can be 1.1 to 2.0 times the average particle size of the powder of poly-L-lysine to which the acid anhydride is added.
[0054] The size of the holes through which the substrate sheet passes in the thickness direction is small, reaching a degree that all or most of the powder of the above-mentioned two-reactive agent type adhesive cannot pass through. In addition, it is preferably disintegrated, absorbed or discharged in the body within a period of the same degree as the above-mentioned medical two-reactive agent type adhesive, for example, 0.3 times to 3 times, and particularly 0.5 times to 2 times. However, according to the use, it can also be decomposed quite early compared with the above-mentioned medical two-reactive agent type adhesive. For example, it can also be considered that due to the regeneration of the biological tissue at the wound site, although bonding is required, it is not so necessary to use fiber materials for reinforcement. On the other hand, even if the fibers constituting the substrate sheet remain in the biological tissue for a relatively long period, it is possible not to have an adverse effect on the function of the biological tissue.
[0055] The substrate sheet may be a sheet of fiber products such as non-woven fabric, woven fabric, knitted fabric, mesh sheet, etc., and may also be a non-textile open-cell porous sheet such as a sponge (foam) with continuous pores, a suede (complex of fine fibers), a grid or net with fine pores, a honeycomb, etc.
[0056] The thickness of the substrate sheet can be set, for example, to 10 μm to 1000 μm (1 mm), 15 μm to 500 μm (0.5 mm), and particularly to 20 μm to 300 μm. In particular, when the substrate sheet is a sheet of a fiber product composed of relatively strong fibers, the thickness can be set to 10 μm to 150 μm, particularly to 20 μm to 100 μm or 20 μm to 50 μm.
[0057] In a preferred embodiment, the substrate sheet is a mesh sheet or braided fabric woven from biodegradable filaments (long fibers), and in particular, in order to suppress elasticity, it is a mesh sheet or braided fabric woven by warp knitting (longitudinal knitting; tricot, Raschel, etc.). The mesh sheet or braided fabric can be a single-layer sheet, or a sheet with multiple braids overlapped, or a braided fabric formed by double knitting, three-dimensional knitting, etc., depending on the situation.
[0058] When forming a mesh sheet, the diameter of the constituent silk thread outside the nodule portion can be, for example, 20 to 300 μm. In addition, taking into account the required shape stability, flexibility, etc., it can be appropriately made into a multifilament or a monofilament. The mesh opening (diameter of the opening) of such a mesh sheet can be, for example, 0.1 mm to 3 mm, especially 0.2 mm to 2 mm. In addition, the opening ratio (the value of the total area of the opening divided by the overall area) of the mesh sheet can be, for example, 50 to 95%, especially 60 to 90%. If it is such a mesh sheet, it can support the adhesive resin layer while minimizing the thickness and weight, and can increase the reinforcement effect.
[0059] In the case of a woven fabric sheet, the opening ratio (the value of the total area of the openings based on the knitting holes divided by the overall area) can be, for example, 20 to 50%. In addition, the yarn (braiding yarn) constituting the woven fabric can be made of multifilament or short fiber yarn, so that the void ratio can be, for example, 30 to 80%.
[0060] In a preferred embodiment, the substrate sheet is a nonwoven fabric or paper made of biodegradable fibers, particularly a substrate sheet made of multifilaments (long fibers) or staple fibers (short fibers) made of biodegradable polymers and manufactured by needle punching, spunlace, spunbonding, papermaking, etc.
[0061] In a preferred embodiment, the substrate sheet is a fiber product sheet or a mesh sheet with fine meshes, and in order to facilitate the retention of the powder of the medical two-reactive agent adhesive and the bonding with the powder, it has fine fiber bundles, raised parts, piles, etc., or fine concave-convex structures, etc. at least near the surface.
[0062] In a preferred embodiment, when the surface and / or the cross section (i.e., at least one of these) of the porous sheet based on a fiber product or a non-fiber product constituting the substrate sheet is observed with an optical microscope, the diameter of the larger pores is 500 μm or less, 400 μm or less, or 300 μm or less. In a specific embodiment, the average pore diameter (median diameter; D50) of the pores with a diameter of 1 μm or more observed with an optical microscope is, for example, 20 to 150 μm. The porosity (%; porosity; volume ratio of pores) of the substrate sheet is, for example, 50 to 97% or 60 to 95%.
[0063] As biodegradable polymers constituting the substrate sheet, proteins such as collagen, other amino acid polymers, polysaccharides or derivatives thereof, aliphatic polyesters such as aliphatic hydroxy acid polymers or derivatives thereof, polyvinyl alcohol (PVA) or derivatives thereof, etc. can be cited. Here, "derivatives" refer to substances that have been given or adjusted properties such as biodegradability by the introduction, oxidation, reduction, atomic substitution, etc. of functional groups. Such biodegradable polymers are all hydrophilic and have good adhesion to the above-mentioned two-reactive agent type adhesive.
[0064] As preferred biodegradable polymers, collagen, dextran, dextrin, aliphatic polyester and polydioxanone (PDS) can be mentioned. As preferred aliphatic polyesters, polyglycolic acid (PGA), glycolic acid / lactic acid copolymer (PLGA), polylactic acid (PLLA, PDLLA) and lactic acid / caprolactone copolymer can be mentioned. Since the biodegradable polymers cited here will also disintegrate from the inside by hydrolysis, etc., it is easy to set it as a whole to decompose after a specified period, so it is preferred. In addition to the above, other lactic acid polymers, decapeptides, etc. can also be preferably used, and polycaprolactone (PCL), polyglucose ester (copolymer of trimethylene carbonate and glycolide), oxidized cellulose, chitosan or its derivatives, etc. can also be used.
[0065] Specific examples of the biodegradable polymer include the following commercially available products from BMG Corporation.
[0066] (1) Polyglycolic acid (PGA): The melt flow rate (MFR) at 240°C and 10 kg load is 3.0 to 9.0 g / 10 min.
[0067] (2) Poly-L-lactic acid (PLLA): Weight average molecular weight M based on GPC-light scattering method W The molecular weight of the polyol is 200,000 to 280,000, and the melting point based on the DSC method is 180 to 195°C.
[0068] (3) Glycolic acid / DL-lactic acid copolymer (PGDLLA): The molar ratio of glycolic acid to lactic acid is 20:80 to 30:70, and the weight average molecular weight M based on GPC-light scattering method is W The molecular weight of the polyol was 220,000 to 280,000, and the melting point according to the DSC method was 50 to 60°C.
[0069] (4) L-lactic acid / ε-caprolactone copolymer (LCL)
[0070] LCL (75:25): The molar ratio of L-lactic acid to ε-caprolactone is 70:30 to 80:20, and the weight average molecular weight M based on GPC-light scattering method is WThe molecular weight of the polyol is 400,000 to 800,000, and the melting point according to the DSC method is 150 to 175°C.
[0071] LCL (50:50): The molar ratio of L-lactic acid to ε-caprolactone is 45:55 to 55:45, and the weight average molecular weight M based on GPC-light scattering method is W The molecular weight of the polyol is 200,000 to 600,000, and the melting point according to the DSC method is 80 to 130°C.
[0072] (5) Poly(p-dioxanone) (PDO): The melting point according to the DSC method is 100 to 110° C. The melt flow rate (MFR) at 240° C. and a load of 10 kg is 3.0 to 9.0 g / 10 min.
[0073] In a preferred embodiment, the base sheet is a foam sheet having a continuous pore structure made of a biodegradable resin such as polylactic acid or aliphatic polyester, or a mesh sheet having a plurality of vertical continuous pores formed of a fine honeycomb structure.
[0074] Specific examples of substrate sheets include: collagen sponge sheets ("single layer type" of "Pernac GPlus (registered trademark)" of Gunze Co., Ltd., pressed sheets of "Integran" of Koken Co., Ltd.), collagen fiber sheets ("Collagen Fiber Sheet" of Nippi Co., Ltd.), non-woven fabrics of polyglycolic acid ("NEOVEIL": registered trademark, Gunze Co., Ltd.), fabrics of oxidized cellulose and oxidized regenerated cellulose ("Surge Cell" and "Interseed": registered trademarks, Johnson & Johnson Co., Ltd.), non-woven fabrics of chitin ("Vesquitin": registered trademark, Nipro Co., Ltd.), etc.
[0075] The collagen sponge sheet can be obtained, for example, by adjusting the collagen solution to be acidic, cross-linking with glutaraldehyde, and then freeze-drying and heat-drying, according to the description of Example 3 of Japanese Patent Application No. 4681214.
[0076] In a preferred embodiment, a porous layer including the two-reactant adhesive is formed by fixing the powder of the two-reactant adhesive on at least one surface of the substrate sheet. The thickness of the porous layer can be adjusted by appropriately increasing or decreasing the amount of the two-reactant adhesive powder applied on the substrate sheet. In addition, in the present application, "fixed" includes not only a method of being attached or laminated on the surface of the substrate sheet, but also a method of being present inside the substrate sheet.
[0077] The thickness of the resin layer (adhesive resin layer) formed by the two-reactant adhesive on the substrate sheet after the two-reactant adhesive is fixed on the substrate sheet and dried is, for example, 50 μm to 1000 μm (1 mm), 100 μm to 800 μm (0.8 mm), 150 μm to 600 μm (0.5 mm), and particularly 200 μm to 500 μm. In addition, when the thickness of the substrate sheet is, for example, 15 μm to 500 μm (0.5 mm) or 20 μm to 300 μm, the thickness of the adhesive resin layer can be 0.5 to 20 times, 0.8 to 10 times, 1 to 5 times, etc., the thickness of the substrate sheet. The thickness of such an adhesive resin layer corresponds to the coating amount of the two-reactant adhesive powder when the two-reactant adhesive is fixed on the substrate sheet.
[0078] When such a sheet-like structure adhesive reinforcement material (adhesive sheet) is produced, the amount of the two-reactive agent type adhesive applied (on a dry weight basis) can be, for example, 30 to 500 mg / cm 2 40~400mg / cm 2 , 50~300mg / cm 2 or 60-250 mg / cm 2 , especially 70 to 200 mg / cm 2 , 80~200mg / cm 2 or about 100-150 mg / cm 2 . If the thickness of the porous layer formed by the two-reactive agent type adhesive or the mass per unit area is too large, the flexibility of the sheet-like tissue bonding reinforcement material is reduced. If it is too small, the bonding force and the sealing for preventing leakage have the possibility of becoming insufficient. In addition, the porous layer formed by the two-reactive agent type adhesive on the substrate sheet has good adhesion to the wound site because the thinner the softness is, the better. However, in addition to the above-mentioned bonding force and sealing, the operability of applying the two-reactive agent type adhesive on the substrate sheet will also change according to the coating amount of the two-reactive agent type adhesive and the properties and physical properties of the substrate sheet. Therefore, these factors can be considered comprehensively and the coating amount of the two-reactive agent type adhesive can be appropriately adjusted.
[0079] In a preferred embodiment, the sheet-like tissue adhesive reinforcement material (adhesive sheet) and the substrate sheet used therefor are formed into a flat shape extending along a plane, and can be a product in which sheets of a specified size are overlapped or wound into a roll-like shape. However, it is also possible to form a curved shape in advance according to the shape of the applicable wound site or the affected part. That is, it is possible to form a shape that is curved only in one direction and has a circular arc shape in cross section, or it is possible to form a curved cup shape that forms a part of a spherical surface. In addition, it is possible to form a linear, rod-shaped, bag-shaped, tubular, etc. shape according to the situation.
[0080] In order to fix the powder of the two-reactive agent type adhesive on the substrate sheet using ethanol, the water content of ethanol is preferably set to 3% or less, 2.5% or less, 2% or less, less than 2%, less than 1.5%, less than 1.5%, less than 1% or less than 1%, and particularly to 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less. In addition, the water content of ethanol is set to, for example, 0.1% or more, 0.2% or more, 0.3% or more, or 0.4% or more. In this way, the water content of ethanol can be 0.2-2%, 0.3-1.5%, or 0.3-1%, particularly 0.3-0.8%. As the water content of ethanol becomes higher than the above-mentioned upper limit, it becomes difficult to uniformly fix the mixed powder of the two-reactive agent type adhesive (the powder of aldehyde-modified dextran and the powder of succinic anhydride polylysine) on the substrate sheet. In particular, a mixed powder of a two-reactant type adhesive may become difficult to disperse and may partially or entirely form lumps.
[0081] It is particularly preferred to use ethanol as a solvent (dispersion medium) for fixing the powder of the two-reactive agent type adhesive on the substrate sheet. Low-water-content ethanol having a water content of 0.1% to 2.0% or 0.2% to 1.5%, particularly 0.2% to 1.0%, is used because the mixed powder of the two-reactive agent type adhesive can be well fixed on the substrate sheet. In addition, if ethanol is used, when the sheet-like tissue reinforcement material is used in the human body, problems such as toxicity caused by the recovery / removal of the solvent and the slight residual solvent after drying are eliminated or greatly reduced.
[0082] However, in addition to ethanol, any hydrophilic organic solvent that is volatile and low in toxicity can be used. In particular, substances that can be freely mixed in water (forming a uniform solution in any proportion) and have a boiling point of less than 100°C can be used. As such organic solvents, acetone, 1-propanol and 2-propanol (isopropanol) can be cited. When using hydrophilic organic solvents other than these ethanols, the water content can be set based on the preferred range of the water content of the above-mentioned ethanol. However, according to the degree of hydrophilicity of the organic solvent, the upper limit and lower limit of the water content can be adjusted, especially as described later, so that the degree of plasticization or partial dissolution of partially carboxylated poly-L-lysine becomes the same as when ethanol is used. For example, when acetone is used, the water content can be set to 1 to 3% or 1 to 2%.
[0083] In addition, a mixed solvent of ethanol, acetone, 1-propanol, 2-propanol and other hydrophilic organic solvents can also be used. For example, a solution prepared by adding 2-propanol to ethanol to give 2 to 35% by volume can be used within the above-mentioned water content range for ethanol.
[0084] When making sheet-like tissue adhesive reinforcement material (adhesive sheet), also can add the additive that allows pharmaceutically.Particularly, when the powder of 2 reactive agent type adhesive is fixed on substrate sheet, can use in hydrophilic organic solvents such as ethanol, make the additive dissolve or disperse the material that obtains in advance.As additive, can enumerate: amino acid, sugar, fatty acid, salt, sugar alcohol and surfactant etc.By these additives more than one suitably with 2 reactive agent type adhesive combination, can change the solubility, flexibility, gelation speed, tissue adhesive reinforcement material and the bonding force of biological tissue that absorbs moisture and the hydrogel or substrate sheet that generates when using sheet-like tissue adhesive reinforcement material.
[0085] As ethanol and the like evaporate, the additive changes from being dissolved or dispersed in ethanol and the like to being attached to the surface of the substrate sheet and the surface of the porous layer formed by the two-reactive agent type adhesive, etc. In addition, it is believed that the fixation of the two-reactive agent type adhesive occurs because a part of the powder of the two-reactive agent type adhesive, especially the surface layer of the modified poly-L-lysine powder, is partially dissolved, so it is believed that the additive also enters the solidified part after being temporarily dissolved in this way. It is believed that when the sheet-like structure bonding reinforcement material is used, most of the additive is captured inside the water-containing gel formed by the entry of water.
[0086] Pharmacological components may be added instead of or together with the above-mentioned additives. Examples of pharmacological components include antibiotics, anti-inflammatory agents, blood circulation improvers, steroids, enzyme inhibitors, cytokines, vitamins, enzymes, etc. By making the tissue adhesion reinforcement material contain pharmacological components, it can also be used as a kind of traction delivery system for the purpose of slowly releasing the pharmacological components. That is, it can be used in a manner that the pharmacological components are gradually released from the hydrogel.
[0087] The application and fixation of the two-reactive agent type adhesive to the base sheet for producing the sheet-like tissue adhesive reinforcing material (adhesive sheet) can be performed by any of the following (i) to (iv), for example.
[0088] (i) Discharging the dispersion onto the substrate sheet
[0089] The powder of the two-reactant adhesive is forcibly dispersed in the above-mentioned low-water-content ethanol. Then, the relatively unstable dispersion (suspension) obtained is sprayed, dripped or dropped toward the substrate sheet, especially from above, or ejected by other methods, thereby coating.
[0090] At this time, for example, 1 part by weight of powder of a two-reactant adhesive with an average particle size of 20 to 80 μm is added to 8 to 15 parts by weight of low-water-content ethanol, and stirred by using a small stirring mechanism so that it can be evenly dispersed, and sprayed onto the substrate sheet for coating. For example, a slit coater, a curtain coater, or a spray coater having a stirring mechanism in a liquid storage portion (liquid storage portion) can be used. In the spray coater, an air spraying method based on compressed gas for spraying can be used. For example, a spray gun with a paint stirring device (for example, the "stirrer spray gun" of Anest Iwata Co., Ltd.) can also be used. Electrostatic spraying and ultrasonic coating machines can also be used. In addition, depending on the situation, a syringe-type dispenser can also be used.
[0091] In order to conduct a simple experiment, a dispenser such as a dispensing pipette can be used to appropriately stir the coating with a vibration motor, ultrasonic waves, etc. In addition, in the stirring mechanism here, a coin-type vibration motor used in mobile phones, etc. (for example, a DC vibration motor of φ11 mm produced by Nidec Shinpo Co., Ltd.), a rod-type (pen-type) ultrasonic cleaner (for example, a cleaner equivalent to the UW-A1 series produced by Sharp Corporation), etc. can be used.
[0092] Furthermore, as described later, by adding a biodegradable polymer to ethanol, the viscosity of the dispersion medium containing ethanol can be increased, thereby achieving thickening and stabilization for stably holding the powder of the two-reactive agent type adhesive.
[0093] (ii) The substrate sheet is abutted against the dispersion layer.
[0094] The coating can be performed by spreading the same dispersion as in (i) above on the surface and bringing the substrate sheet into contact with the layer of the dispersion thus formed. The surface on which the dispersion is spread can be a flat surface or a curved surface such as a roller surface. In addition, a non-adhesive surface can be formed by appropriately lining the metal surface with a silicone resin or a fluororesin.
[0095] In order to spread the dispersion evenly on the surface, the same coater and dispenser as in (i) above can be used. That is, a slit coater, curtain coater, spray coater, dispenser, etc. equipped with a stirring mechanism in the liquid storage part can be used. In addition, a roll coater such as a direct gravure coater that transfers the coating to the substrate sheet after coating on the roll surface can also be used.
[0096] In one embodiment, the dispersion liquid identical to the above-mentioned (i) is placed on a non-adhesive flat surface, spread in a manner to form a uniform thickness, and a substrate sheet is covered thereon. For example, the dispersion liquid of the above-mentioned (i) is uniformly coated on a horizontal and flat metal plate lined with a silicone resin or a fluororesin, or on the bottom surface of a club handle or a tray, by a curtain coater, a dispenser, etc. having a stirring mechanism. Then, thereafter, on the layer of the dispersion liquid, it is placed in a manner to cover the substrate sheet. Then, after the removal process of ethanol is directly performed, the substrate sheet and the adhesive resin layer formed on the one side can be peeled off from the non-adhesive surface formed by the lining, etc. At this time, before the drying is completed, the substrate sheet formed with the adhesive resin layer can also be peeled off. In addition, for example, the substrate sheet can also be fixed on the surface of a roller lined with a silicone resin, etc., so that it is sequentially abutted with the surface coated with the dispersion liquid of the above-mentioned (i). At this time, for example, it is also possible to consider using a rubber roller as a coating roller so that it contacts the roller on which the substrate sheet is installed.
[0097] (iii) After applying the powder to the substrate sheet, a dispersion medium is supplied
[0098] Only the mixed powder of the two-reactive agent type adhesive is applied on the base sheet by spraying or the like, and then ethanol is supplied thereto by spraying, dripping or the like.
[0099] At this moment, in order to spray ethanol, for example, also can use common spray bottle.In addition, also can use the needle spray gun (TOMITA ENGINEERING CO., LTD) that quantitative ejection valve mechanism is integrated with spray gun.In addition, in order to be coated with or infiltrate ethanol on substrate sheet, be not limited to spraying, dripping, can also be for example the mode that sponge face, sponge roller and substrate sheet that infiltrate ethanol abut.Further, can also be the mode that ethanol infiltrates in substrate sheet by putting the substrate sheet after coating into ethanol and being placed on the layer that expands thinly.
[0100] (iv) Powder coating after supplying dispersion medium
[0101] Only the powder of the two-component adhesive was sprayed onto the substrate sheet soaked in ethanol.
[0102] In order to pre-impregnate the substrate with ethanol, for example, the substrate sheet can be immersed in ethanol, or ethanol can be uniformly infiltrated into the substrate sheet using the above-mentioned needle spray gun, spray coater, or the like.
[0103] When the two-reactive agent type adhesive is applied / fixed on the substrate sheet as in (i) to (iv) above, particularly when the powder of the two-reactive agent type adhesive is dispersed in ethanol and sprayed as in (i) above, a biodegradable polymer soluble in ethanol such as hydroxypropyl cellulose (HPC) or hydroxypropyl methyl cellulose (HPMC) can be added to the ethanol in advance. For example, 5 to 30% of the weight of the two-reactive agent type adhesive can be added to impart softness and toughness to the two-reactive agent type adhesive layer in the sheet-like tissue adhesive reinforcement material after drying.
[0104] The biodegradable polymer used herein can be used even if it is not completely dissolved in the dispersion medium, but can be used as long as it is uniformly dispersed. In addition, the dissolution or uniform dispersion in the dispersion medium is not limited to the mode of suction with the mixed powder, and can also be mixed in the mixed powder in the form of powder.
[0105] When the adhesive sheet is used for hemostasis, etc., a blood coagulation promoter is added in various ways similar to the addition of the above-mentioned biodegradable polymer, so that the blood coagulation promoter can be contained in the adhesive resin layer, etc. Specifically, a dry preparation of a coagulation initiator such as thrombin, which brings about a hemostatic effect through a thromboplastin-like action, or snake venom hemocoagulase, which is an enzyme hemostatic drug made from snake venom, can be added. The amount of coagulation initiators such as thrombin added can be, for example, 200 to 5000 units (IU) or 500 to 3000 units (IU) in a substrate sheet of 100mm×50mm, that is, 4 to 100 units (IU) or 10 to 60 units (IU) per 1 square centimeter. Depending on the situation, tranexamic acid, epinephrine, or a derivative thereof can also be used as a blood coagulation promoter.
[0106] As the biodegradable polymer added when coating / fixing the two-reactive agent type adhesive on the substrate sheet as described above (i) to (iv), various biodegradable polymers can be cited as other preferred types. As such a biodegradable polymer, collagen and collagen derivatives such as gelatin are particularly preferred from the perspective of preventing cracking of the adhesive resin layer. However, depending on the situation, peptides from organisms such as sericin, casein, and fibrin can be used. In addition, biodegradable polymers that can be used in the formation of the above-mentioned substrate sheet can be used alone or in combination, or in combination with collagen, etc. These can be added in the same various ways as the addition of the above-mentioned biodegradable polymers, and in particular, can be added and mixed in the mixed powder of the two-reactive agent type adhesive in the form of a powder having an average particle size of the same degree as these powders.
[0107] When the two-reactive agent type adhesive is coated / fixed on the substrate sheet in the above-mentioned manner (i) to (iv), by adding a moisturizing component (or plasticizer) such as glycerol, the resulting adhesive resin layer can be given flexibility and the occurrence of cracks during bending can be suppressed. The amount of the moisturizing component added can be, for example, 0.5 to 30% or 1 to 25%, particularly 2 to 15% or 2 to 10%, based on the weight of the two-reactive agent type adhesive. As moisturizing components that can be added, in addition to glycerol, propylene glycol, 1,3-butylene glycol, 1,2-pentanediol, 1,2-hexanediol, polyethylene glycol, sorbitol, maltitol, sodium dl-pyrrolidonecarboxylate, sodium lactate, polyglycerol, sodium hyaluronate and trimethylglycine can also be mentioned. These moisturizing components can be added, for example, by mixing with the mixed powder of the two-reactive agent type adhesive.
[0108] As in the above (i) to (ii), in order to apply the powder of the two-reactant type adhesive on the substrate sheet, or the bottom surface of the handle of a golf club, a tray, etc. in a state dispersed in ethanol, etc., a slit coater or a spray gun having a stirring mechanism in a liquid storage part, etc. can be used. In addition, at this time, a moving table or a conveyor belt can be used for relative movement between the liquid ejection part and the substrate sheet.
[0109] When fixing is performed by the above-mentioned methods (iii) to (iv), a powder hanging machine that allows the powder to fall evenly from a sieve-like mesh or a plurality of small holes, or a spray gun-type or dispenser-type powder spraying device can be used to apply the powder of the two-reactant type adhesive on the substrate sheet. In this case, the electrostatic coating method and the flow dipping method used in powder coating can be appropriately used. For example, a powder spraying part having a plurality of small holes arranged in a narrow and long area is provided at the bottom of the powder storage tank, and the substrate sheet is moved in a direction that crosses the narrow and long powder spraying part while the powder is falling, thereby enabling coating. At this time, a high voltage is applied between the screen part and the base surface on which the substrate sheet is placed, and a uniform distribution can be achieved by an electrostatic coating method. For example, a device with a mechanism such as the "electrostatic screen powder hanging machine" of Mori Industry Co., Ltd. can be used. In addition, for example, the powder can also be applied by adding the substrate sheet (flow dipping method) while the powder is made to flow using dry compressed air. Furthermore, in the case of (iii) above, a mass of powder may be placed on a substrate sheet and then applied by spreading the powder evenly using a rubber roller, a rubber blade (squeegee), or the like.
[0110] In a preferred embodiment, by using a horizontal drive mechanism (X-axis drive mechanism) in the left-right direction of a servo motor or the like and a horizontal drive mechanism (Y-axis drive mechanism) in the front-back direction of a servo motor or the like, coating can be performed while continuously or sequentially moving relative to each other between the powder ejection unit and the substrate sheet. That is, an XY-axis-ejection unit drive device (for example, a device of a "desktop coating machine" of NCC Co., Ltd.) in which the powder ejection unit is installed at the driving end of an XY-axis drive mechanism based on an X-axis drive mechanism and a Y-axis drive mechanism can be used. In addition, the substrate sheet can be placed on an XY workbench equipped with an XY-axis drive mechanism, and coating can be performed by a fixed-position powder ejection unit.
[0111] In a preferred embodiment, the medical powder spraying device of Japanese Patent Special Opening 2016-063919, or the powder spraying device recorded in Japanese Patent Special 2017-222915 can be used. These powder spraying devices are pistol-shaped spray guns that use compressed air to spray, so that the operator can lift the opening and closing operation of spraying with one hand. In order to use these powder spraying devices and the powder of 2 reactive agent type adhesive is coated on the substrate sheet, the above-mentioned XY axis-ejection portion drive device, XY workbench or robot arm, other mobile platforms or conveyor belts etc. can be used. In addition, at this time, electrostatic coating method etc. can also be used.
[0112] like Fig. 9 As shown, the powder spraying device described in Japanese Patent Application No. 2017-222915 comprises: (i) a funnel component 1 capable of mounting a powder container 7 on the upper portion or integrally provided with the powder container 7; (ii) a first three-way joint 3 having a first opening 31 connected to a discharge port 11B at the lower end of the funnel component 1; an air flow supply pipe 41 and a delivery pipe 42 respectively connected to the second and third openings 32 and 33 of the first three-way joint 3; a housing 5 for accommodating these components; (iii) a vibration motor 2 mounted on the funnel component 1; and (iv) a branch from the air flow supply pipe 41 so as not to pass through the first three-way joint 11B. (v) an opening and closing mechanism 6 for switching the compressed gas between a coating state (on state) and a standby state (off state), wherein the coating state (on state) is a state in which the compressed gas is delivered through the airflow supply pipe 41, the interior of the first three-way joint 3 and the coating flow path 4A through the delivery pipe 42, and is also delivered through the bypass airflow pipe 8, and the standby state is a state in which the compressed gas is delivered only through the bypass airflow pipe 8, and the funnel part (1) and the first three-way joint (3) are mounted relative to the shell (5) so as to be shaken and vibrated.
[0113] More generally, the powder spraying device comprises: a storage part capable of storing powder; a vibration mechanism capable of vibrating the storage part before spray coating starts; a delivery path for delivering the powder dropped from the storage part to the nozzle together with the compressed gas in the coating state (on state); and a bypass path for delivering the compressed gas to the nozzle without passing through the position where the powder drops from the storage part in the standby state (off state). Such a powder spraying device is suitable for coating powder having a random shape as described above, such as the two-reactant type adhesive used in particular in the present application, and a powder that easily absorbs moisture and blocks the delivery path.
[0114] After applying the two-reactant adhesive on the substrate sheet as described in (i) to (iv) above, the ethanol can be recovered and dried while being appropriately heated in a nitrogen atmosphere, for example, while being left at rest. For example, the "shelf-type powder drying system SDP-500" (Strain: Creative Chemical Research Institute) can be used. Alternatively, a reduced pressure dryer (vacuum dryer) equipped with a constant temperature heating mechanism can be used.
[0115] After drying, the obtained sheet-like tissue adhesive reinforcement material (adhesive sheet) can be sterilized by ultraviolet rays (UV), electron beams, ethylene oxide gas (EOG) or gamma rays. In addition, in order to avoid moisture absorption, it can be stored in a desiccator or sealed and stored in a bag composed of a laminated film with an aluminum layer.
[0116] In the coating / fixing method described above, although a mixed powder of a two-reactant adhesive is used, for example, the above-mentioned powder spraying device can also be used to spray-coat the powder of modified poly-L-lysine (SAPL) on the substrate sheet, and then evenly spray anhydrous ethanol, spray-coat the powder of aldehyde-modified dextran (AD) thereon, and then spray anhydrous ethanol.
[0117] The sheet-like tissue adhesive reinforcement material (adhesive sheet) obtained as described above comprises: a substrate sheet having biodegradability and a porous interconnected structure; and an adhesive resin layer fixed and formed thereon. The adhesive resin layer comprises: a first reactant containing aldehyde-deoxyglucan and a second reactant containing partially carboxylated polylysine, and comprises a granular structure (particles) of powder from the first reactant and a linking layer from the second reactant. The linking layer links the granular structure (particles) of the first reactant to each other and fixes them on the substrate sheet.
[0118] As for reference example 1 Fig.14As shown in the photo of the upper section, it is believed that when manufacturing the adhesive sheet, the second reactant (partially carboxylated polylysine) swells in a dispersion medium such as anhydrous ethanol by absorbing the dispersion medium, becomes a paste with adhesion and some fluidity, and links the powder of the first reactant (aldehyde-deoxyglucan). In addition, it is believed that it is bonded to the substrate sheet at the same time and partially enters into a plurality of interconnected holes of the substrate sheet. Then, it is inferred that: by removing the drying operation of the dispersion medium, the resin layer is mainly bonded to the substrate sheet with the anchoring effect (mechanical bonding) based on the part entering the interconnected holes when being formed on the substrate sheet. On the other hand, it is believed that the powder of the first reactant (aldehyde-deoxyglucan) also maintains a general shape even in the dispersion medium, thus forming a granular structure (particles) in the resin layer when bonding.
[0119] Example
[0120] Hereinafter, although embodiment of the present invention is described by way of examples, these are not intended to limit the scope of the present invention.
[0121] <Example 1> Preparation of adhesive sheet based on coating dispersion on cotton fibrous collagen sheet 0.5 g of mixed powder of two-reactant adhesive was added to 6 mL (4.9 g) of "anhydrous" ethanol (ethanol 99.5 vol% or more, Wako grade 1) placed in a glass container (10 mL vial), plugged, and evenly dispersed by ultrasonic stirring. Collagen sponge sheet was used as the base sheet. Specifically, "Integran" "pressed sheet" (100 mm × 50 mm, 0.2 g cotton fibrous collagen sheet) of Koken Co., Ltd. was used directly.
[0122] The website of "Integran" of Koken Co., Ltd. states that "Integran is an absorbent local hemostatic material obtained by spinning highly purified calf dermis telopeptide collagen (collagen that can be dissolved by protease and has its main antigenic expression sites removed) into cotton fibers and chemically cross-linking them with a polyepoxide compound."
[0123] After the mixture was uniformly dispersed as described above, the stopper of the glass container was opened. Then, while appropriately continuing ultrasonic stirring, the mixture was pipetted with a dispensing pipette (MS Equipment). t(Co., Ltd.)'s P-type pipette (Pipetteman) P000, equipped with a 1mL pipette tip) sucks the dispersion in the glass container in sequence and applies it to the entire surface of the substrate sheet. The coating is carried out by evenly dripping on the above-mentioned 5cm×5cm substrate sheet. Then, it is placed in the air at room temperature overnight to dry it, and then placed in a vacuum dryer and decompressed and exhausted at room temperature to completely remove ethanol and make the overall moisture content less than 0.2%. In this way, the thickness of the adhesive resin layer with bumps becomes about 300 to 350μm (0.3 to 0.35mm). In addition, in this case, except for the peripheral edge of the substrate sheet, it is considered that the amount of adhesive resin per square centimeter is 15 to 20mg. This amount is comparable to the optimal single coating amount of 20 to 30mg / cm when the powder of the two-reactant type adhesive is directly used. 2 The lower limit value of is roughly equal to or slightly less than it.
[0124] The adhesive sheet ("LYDEX sheet / collagen substrate") obtained in the manner described above is slightly hard, but by winding it into a roll, it can be formed into a roll with a diameter of about 2 cm. In addition, at this time, the adhesive resin will not fall off, and cracks will not occur in the adhesive resin layer. When the surface and cut surface of the adhesive sheet are observed with a high-performance stereo microscope ("digital microscope VHX-5000" system manufactured by KEYENCE), a mixed powder of the two-reactant type adhesive is densely formed over the entire surface, especially a tiny protrusion structure believed to be a powder from aldehyde-modified dextran.
[0125] In addition, the mixed powder of the two-reactive agent type adhesive is a mixed adhesive powder (average particle size of 80 μm) obtained by mixing a powder of aldehyde-modified dextran having an aldehyde group introduction amount of 0.28 per glucose / unit and a powder of succinic anhydride-added polylysine having a residual rate of free amino groups of 89.5% at a weight ratio of 4 / 1. These production methods are as described in International Publication WO2008 / 066182 (Patent Document 1). That is, the production method obtained in the manner as follows 1) to 3).
[0126] 1) Preparation of powdered aldehyde-dextran (first reactant; AD)
[0127] 400g of dextran (Meito Sangyo Co., Ltd., "Dextran 70") with a molecular weight of 70,000 was dissolved in 1600mL of ion exchange water, and 50g of sodium periodate (molecular weight 213.89) was dissolved in 800mL of ion exchange water and added, and reacted while stirring for 3 hours in a 50°C water bath. Then, after the reacted solution was dialyzed, it was filtered with a 0.45μm filter and dried. Further, a small pulverizer (Wonder Crash Mill D3V-10, Osaka Chemical Co., Ltd.) was used for pulverization to obtain powdered aldehyde-dextran (2.5 / 20). In addition, (2.5 / 20) represents the feeding ratio constituting the aldehyde-dextran (sodium periodate / dextran 70). The amount of aldehyde group introduced per sugar residue amount (mole) in the obtained aldehyde-dextran is 0.28. In addition, the amount of aldehyde group introduced is determined by redox titration. Specifically, 20mL of 0.05mol / L iodine aqueous solution, 10mL of 10mg / mL aldehyde-dextran aqueous solution and 20mL of 1mol / L sodium hydroxide aqueous solution are placed in a 100mL conical flask and stirred at 25°C for 15 minutes. Then, 15mL of 6v / v% sulfuric acid aqueous solution is added and titrated with 0.1mol / L sodium thiosulfate aqueous solution. The endpoint is the time point when the reaction system becomes colorless and transparent, and the indicator is a starch aqueous solution. When the particle size of the powder is evaluated using a stereomicroscope, the average particle size is 90μm. Further, the result of observing the surface properties by electron microscopy is the formation of a porous body. The average aspect ratio (the ratio of the major axis to the minor axis) is about 1.6.
[0128] The amount of aldehyde group introduced per sugar residue amount (mole) in the obtained aldehyde-dextran is 0.28. In addition, the amount of aldehyde group introduced is determined by redox titration. Specifically, 20 mL of 0.05 mol / L iodine aqueous solution, 10 mL of 10 mg / mL aldehyde-dextran aqueous solution and 20 mL of 1 mol / L sodium hydroxide aqueous solution are placed in a 100 mL conical flask and stirred at 25 ° C for 15 minutes. Then, 15 mL of 6 v / v% sulfuric acid aqueous solution is added and titrated with 0.1 mol / L sodium thiosulfate aqueous solution. The endpoint is the time point when the reaction system becomes colorless and transparent, and the indicator is a starch aqueous solution.
[0129] 2) Preparation of succinic anhydride treated polylysine (second reactant; SAPL)
[0130] 10 g of succinic anhydride (nacalai tesque) was added to 400 g of a 25 wt % ε-polylysine aqueous solution (molecular weight 4,000, Chisso Co., Ltd.), and the mixture was reacted at 50 ° C for 1 hour. After filtering the reacted solution with a 0.45 μm filter, it was dried. Further, a small pulverizer (Wonder Crash Mill D3V-10, Osaka Chemical Co., Ltd.) was used for pulverization to obtain powdered succinic anhydride-treated polylysine. For the obtained succinic anhydride-treated polylysine, the residual rate of free amino groups (side chains and terminal amino groups that are not related to the formation of peptide bonds) was found to be 89.5%. In order to carry out the determination, after dissolving in water, a ninhydrin solution and an acetic acid / sodium acetate buffer solution of pH 5.5 were added, and after heating in a boiling water bath for 3 minutes, the sample solution was quenched to form a sample solution. Then, the ultraviolet visible absorbance determination method of the Japanese Pharmacopoeia was used to test the absorbance at a wavelength of 570nm to obtain the amino content in the sample solution. When the obtained powdered succinic anhydride treated polylysine was evaluated using a stereomicroscope in the same manner as the above-mentioned aldehyded dextran, it was a porous body with roughly the same random shape. In addition, the average particle size was 80μm. The average aspect ratio was about 1.7.
[0131] For the obtained succinic anhydride treated polylysine, when the residual amino group rate was quantitatively measured, it was 84.7%. In addition, the residual amino group rate was quantitatively measured in the following manner. First, the powdered succinic anhydride treated polylysine was dried and dissolved in water. Thereafter, ninhydrin solution and acetic acid / sodium acetate buffer of pH 5.5 were added, heated in a boiling water bath for 3 minutes, and then quenched to make a sample solution. Then, the ultraviolet visible absorbance determination method of the Japanese Pharmacopoeia was used to test the absorbance at a wavelength of 570nm to obtain the amino group content in the sample solution.
[0132] 3) Mixed adhesive powder
[0133] The above-mentioned powdered aldehyde-modified dextran and powdered succinic anhydride-treated polylysine were mixed at a weight ratio of 4 / 1 so that the molar ratio of aldehyde groups to amino groups in the mixed adhesive powder (average particle size of 80 μm) was approximately 1. The obtained mixed adhesive powder is shown in FIG. The bulk density of the mixed adhesive powder is 420 mg / cm 3. In addition, the mixed adhesive powder is sealed and stored in a manner to maintain a moisture content of 0.5 to 1.0%. In the present application, the mixed adhesive powder is also appropriately referred to as "Lydex (registered trademark)". In addition, unless otherwise specified, the powder of the above-mentioned reaction charging ratio and mixing ratio is used. That is, succinic anhydride-treated polylysine obtained by reacting 10 g of succinic anhydride with 100 g of ε-polylysine is used, and the charging weight ratio of sodium periodate / dextran 70 during the hydroformylation of dextran is set to 2.5 / 20, and the hydroformylated dextran (AD) and succinic anhydride-treated polylysine (SAPL) are mixed at a weight ratio of 4 / 1, and a mixed powder ("LYDEX2.5 / 20") of a two-reactant type adhesive is used.
[0134] <Example 2> Effect of water content of dispersion medium
[0135] The mixed powder of the above-mentioned two-reactant type adhesive is dispersed in ethanol with different water contents, and the dispersion is observed. That is, as the dispersion medium, 6 mL of ethanol with water contents adjusted to less than 0.5%, 1%, 2%, 5% and 10% are prepared (that is, dispersion media with five levels of water content). Then, 0.5 g of the same mixed powder of the two-reactant type adhesive used in the above-mentioned Example 1 is added to the above-mentioned glass container (10 mL vial), and after ultrasonic stirring in the same manner, it is placed in a covered glass petri dish (φ32×20 mm) for observation. Figure 1 A group of photos summarizes the situation.
[0136] In addition, "0.5% or less" means that commercially available anhydrous ethanol (ethanol 99.5 vol% or more) is used directly. After this experiment, it was confirmed that the water content in the same type of anhydrous ethanol products is about 0.3-0.5%. In addition, the hydrous ethanol with a water content of 1% to 10% is the hydrous ethanol with a calculated amount of water added, assuming that the water content of commercially available anhydrous ethanol is 0.4%.
[0137] like Figure 1 As shown in the figure, when the water content is 5% or more, the phase of the powder containing the two-reactant type adhesive is agglomerated, so that the two-reactant type adhesive cannot be dispersed in a manner that is diffused throughout the dispersion medium (hydrous ethanol). In addition, when the water content is 2%, although it can be dispersed in a manner that is diffused throughout the dispersion medium, it will immediately separate into fine phases and it is difficult to disperse it uniformly. On the other hand, when the water content is 1%, although it can be dispersed roughly uniformly, Figure 1 In the state shown in , partial phase separation was observed after standing for about 10 seconds. In contrast, when using "anhydrous ethanol" whose water content is believed to be 0.3 to 0.5%, even after being stirred and left to stand, phase separation was not observed by naked eye until about 10 seconds.
[0138] from Figure 1 The results show that the water content of ethanol needs to be at least 2% or less or 1% or less, preferably 1% or less, and more preferably about 0.5%. As described later, the mechanism and reason for the significant influence of the water content were further studied through experiments.
[0139] <Example 3> Evaluation of hemostatic effect
[0140] The hemostatic effect on incised tissue was evaluated using an adhesive sheet ("LYDEX sheet / collagen base") having a cotton fibrous collagen sheet ("Integran" "Pressed sheet" 100 mm x 50 mm manufactured by Koken Co., Ltd.) as a base sheet.
[0141] <Example 3-1> Adhesive sheet of Example 1
[0142] Using the adhesive sheet obtained in Example 1, the hemostatic effect was evaluated as follows.
[0143] The upper abdomen of a Japanese white male rabbit was cut open in the middle to expose the liver. The outer left lobe of the liver was excised to a length of about 4 cm, and the hemostasis was gently pressed with a gauze that had been weighed in advance. In this way, the amount of bleeding before application was obtained and recorded, and gushing bleeding was confirmed. Then, the hemostatic sheet ("LYDEX sheet / collagen substrate") obtained by Example 1 and "TACHOSIL" (registered trademark, CSL Behring Co., Ltd.), which is a commercially available hemostatic sheet, were used to stop bleeding.
[0144] The hemostatic treatment was performed by gently pressing and adhering the hemostatic sheet to the incision according to the principle of compression hemostasis. However, when the hemostatic treatment was performed based on the hemostatic sheet of Example 1, a small amount of physiological saline was sprayed as needed. That is, when it was confirmed that a part of the two-reactive agent type adhesive remained in the state of powder without becoming a hydrogel, the physiological saline was sprayed to complete the gelation.
[0145] The amount of bleeding was calculated by absorbing the leaked blood with gauze and the difference in weight before and after application according to the following formula. The results are shown in the following Tables 1 and 2.
[0146] Hemostasis rate (%) = (before application - after application) / before application × 100
[0147] Adhesive sheet of Example 1
[0148]
Table 1
[0149]
[0150] Commercially available hemostatic tablets ("TACHOSIL")
[0151]
Table 2
[0152]
[0153] From the results of Tables 1 to 2 above, it can be seen that no significant difference in the average value of the hemostatic rate was found when the adhesive sheet ("LYDEX sheet / collagen substrate") of Example 1 of the present application was used and when a typical commercially available hemostatic sheet was used. However, in "Trial number 5" of Example 1 of the present application, the hemostatic rate became an extremely low value. This is considered to be because when the hemostatic sheet is made by manual work, there are extremely thin parts of the adhesive resin layer. That is, it is speculated that if the process of making the hemostatic sheet by using a slit coater with a stirring function is improved, or if defective parts such as thin resin layers are eliminated through an inspection process, very good hemostatic performance can be obtained. In addition, taking into account factors such as errors during the hemostatic operation, when the lowest value is removed, it is believed that the adhesive sheet of Example 1 of the present application is superior to the commercially available hemostatic sheet.
[0154] <Example 3-2> Adhesive sheet formed by applying powder using a dispenser
[0155] On the same substrate sheet ("Integran" "Pressed Tablet" 100 mm x 50 mm, manufactured by Koken Co., Ltd.) as used in Example 1, 6 mL (4.9 g) of "anhydrous" ethanol (ethanol 99.5 vol% or more, Wako Grade 1) was uniformly applied over the entire surface using a spray-type dispenser. Immediately thereafter, 0.5 g of the same mixed powder of the two-reactant adhesive ("LYDEX 2.5 / 20") as used in Example 1 was uniformly applied over the entire surface of the substrate sheet. Then, the same drying operation as in Example 1 was performed to obtain an adhesive sheet.
[0156] The ethanol and mixed powder were applied using a coating device ("table plate coating machine" of NCC Co., Ltd.) with a spray dispenser mounted on the driving end of the XY axis drive mechanism. That is, the spray dispenser was swung in the left-right direction while performing a scanning action in the front-back direction in sequence, so that the entire surface was evenly coated.
[0157] When the hemostasis rate was evaluated by the same method / step as in Example 3-1, a hemostasis rate of 90% or more was obtained.
[0158] <Example 3-3> Adhesive sheet containing thrombin
[0159] Dry thrombin powder containing 2000 IU of thrombin was added to 0.5 g of the mixed powder of the same two-reactant adhesive used in Example 1 ("LYDEX 2.5 / 20") and uniformly mixed. Then, an adhesive sheet was prepared in exactly the same manner as in Example 3-2 except that the mixed powder to which thrombin was added was used.
[0160] When the hemostasis rate was evaluated by the same method and procedure as in Examples 3-1 to 3-2, a hemostasis rate of 95% or more was obtained.
[0161] <Example 4> Adhesive sheet using mesh sheet as base sheet
[0162] Poly-L-lactic acid (PLLA) (weight average molecular weight M based on GPC-light scattering method) produced by BMG Corporation was used. W The molecular weight of the composite material was 200,000 to 280,000, and the melting point according to the DSC method was 180 to 195° C.), and two types of mesh sheets (spun and woven) manufactured by Gunze Co., Ltd. were used as the base sheet.
[0163] <Example 4-1>
[0164] The first type of mesh sheet ("PLLA mesh density") is a single-layer knitted fabric in which a multifilament (167 dtx × 24) is knitted through tricot knitting (warp knitting, single bar warp plain weave knitting (Denby knitting)) so that the diameter of each opening (mesh hole) based on the knitting hole becomes about 0.8 mm. The second type of mesh sheet ("PLLA mesh coarse") is a single-layer knitted fabric in which a multifilament (280 dtx × 12) is knitted through tricot knitting (warp knitting, single bar warp plain weave knitting) so that the diameter of each opening (mesh hole) based on the knitting hole becomes about 1.5 to 2 mm.
[0165] Using the first type of mesh sheet ("PLLA mesh density"), Figure 4An adhesive sheet ("LYDEX sheet / PLLA mesh density") is made according to the steps shown in a set of photos. First, the two types of mesh sheets mentioned above are cut into 2.5×5 cm and folded in half, and the surface side and the back side are welded to each other at the left and right edges using an ultrasonic sealer. On the other hand, a dispersion of the same two-reactant adhesive as used in Example 1 is prepared (0.5g "LYDEX 2.5 / 20" + 6mL anhydrous ethanol). Then, after preparing the dispersion, it is immediately transferred from a 10mL vial to the bottom of a horizontally placed fluororesin culture dish (PTFE culture dish; inner diameter 50mm). At this time, the transfer is made so that the coating is evenly spread in order to diffuse with a uniform thickness. Then, the folded mesh sheet is covered on the layer of the dispersion placed on the bottom of the culture dish. Then, in exactly the same way as in Example 1, vacuum drying is performed at room temperature so that the overall moisture content is less than 0.2%.
[0166] As a result, we get Figure 4 The right half of the two photos shows the adhesive sheet ("LYDEX sheet / PLLA mesh density"). Figure 4 The right end photo shows the adhesive resin forming surface (upper side during dipping / drying). Figure 4 The second photo from the right shows the surface on the substrate side (the lower side during immersion / drying). As shown in these photos, even by covering the layer in which the dispersion liquid is diffused with a substrate sheet (the above-mentioned "(ii) contact of the substrate sheet with the layer of the dispersion liquid"), an adhesive resin layer can be formed on one side. The thickness of the adhesive resin layer can be about 300 to 350 μm (0.3 to 0.35 mm), the same as in Example 1.
[0167] However, the surface on the substrate side (back surface) also has adhesive properties in the presence of moisture. Figure 4 As can be seen from the right end photograph, this is believed to be caused by applying adhesive resin on the entire circumference of each thread portion of the mesh sheet.
[0168] <Example 4-2>
[0169] Similarly, we tried to use a coarse mesh sheet ("PLLA coarse mesh") to produce a sheet-like tissue bonding reinforcement material in exactly the same way. Figure 4 The same set of photos Figure 5 Above. Figure 5 As shown above Figure 4 In the same manner as in the case of Example 4-1, an adhesive resin layer can be formed on one side of the mesh sheet (the lower side during dipping / drying). However, the thickness of the adhesive resin layer is relatively uneven, resulting in the formation of thin portions in a dotted manner. It is believed that if the coating method is improved, a coating method that can be used in the same manner as in Example 4-1 can be obtained.
[0170] <Example 4-3>
[0171] On the other hand, using polyglycolic acid (PGA) of BMG Co., Ltd. (melt flow rate (MFR) at 240°C and 10kg load is 3.0 to 9.0 g / 10min), a third type of mesh sheet ("PGA mesh sheet") manufactured (spun and woven) in exactly the same manner as the above-mentioned "first type of mesh sheet ("PLLA mesh density")" was purchased from Gunze Co., Ltd. Then, an adhesive sheet ("LYDEX sheet / PGA mesh") was prepared in exactly the same manner as the above-mentioned "PLLA mesh density". As for the properties of the mesh sheet, it is believed that when polyglycolic acid (PGA) is used, it is exactly the same as when poly-L-lactic acid (PLLA) is used.
[0172] <Example 5> Sealing effect
[0173] The sealing effect against air leakage was evaluated by the following procedures (1) to (4) using the adhesive sheets obtained in Examples 1 and 4-3. Here, four materials shown in Table 3 and in the item "(3) Application to Sealing" were used as comparative examples.
[0174] (1) Preparation of experimental animals
[0175] The rabbit (Japanese white male rabbit) was generally anesthetized and the chest was opened. The airway was secured by a special mouthguard and the breathing was maintained by an artificial respiration device. The respiratory rate was set to 15 times / minute and the inlet pressure (inspiratory pressure) was set to 10 cmH2O.
[0176] (2) Preparation of leakage model
[0177] After partially removing the left posterior lobe, the air intake pressure was increased to 30 cmH2O by declamping and dripping saline on the lung section to confirm the presence of air leakage. If the number of air leakage locations was less than four, an injection needle (18G) was inserted into the section to make the total number of air leakage locations four, thereby creating an air leakage model.
[0178] (3) Application of sealing
[0179] As a seal to prevent air leakage, the adhesive sheet of Example 1 of the present application ("LYDEX sheet / collagen sponge"), the adhesive sheet of Examples 4-3 of the present application ("LYDEX sheet / PGA mesh"), and the seals of each comparative example are used and applied to the cut surface (affected area) through the following steps.
[0180] Adhesive sheets of Examples 1 and 4-3 of the present application (A-1 and A-2 in Table 3)
[0181] Cut into 3 mm squares, apply to the leaking area and gently press to bond. At this time, similar to the above-mentioned confirmation of the hemostatic effect, if it is confirmed that a part of the two-reaction type adhesive has not become a hydrogel and remains in a powder state, spray physiological saline to promote hydrogelation.
[0182] · 2-reactant adhesive (LYDEX) powder (B-1 and B-2 in Table 3)
[0183] The powder of the two-reactant adhesive (LYDEX) was spray-coated on the cut surface, and physiological saline was dripped appropriately to make it completely gelled without leaving any powder. The spray coating used the powder spraying device described in Japanese Patent Application No. 2017-222915 (this application Fig. 9 In addition, the coating amount (mass per unit area) of the adhesive resin was slightly larger than that of the adhesive sheets of Examples 1 and 4-3, which was 25 mg / cm 2 .
[0184] Here, as the reactive adhesive (LYDEX), in Test No. B-1, the above-mentioned "LYDEX 2.5 / 20" used in all other examples of the present application was used, and in Test No. B-2, "LYDEX 4.0 / 20" was used. This is to adjust the feed ratio of the aldehyde-formyl dextran (sodium periodate / dextran 70) from "2.5 / 20" to "4.0 / 20", and adjust the weight ratio of the aldehyde-formyl dextran to the succinic anhydride-treated polylysine so that the molar ratio of the aldehyde group to the amino group is approximately 1.
[0185] Fibrin paste (B-3 in Table 3)
[0186] As shown in the attached document, a mixed solution of "Bolheel for tissue adhesive" produced by KMBiologics Co., Ltd. and a solution A / solution B was applied to the cut surface (affected part) using the attached double syringe ("Bolheel Spray Set Type: End Spray").
[0187] PGA mesh + fibrin paste (B-4 in Table 3)
[0188] The mesh sheet of polyglycolic acid (PGA) ("PGA mesh") used in Example 4-3 was cut into 5 mm squares. Then, using the "Bolheel preparation unit friction spray syringe set", after applying liquid A on the cut surface, the finely cut PGA mesh sheet was attached to the leaking position, and then the mixed solution of liquid A / liquid B was applied to the cut surface.
[0189] (4) Air leakage test based on pressurization
[0190] The pressure was increased stepwise to a maximum of 50 cmH2O to check for leaks. If leaks were confirmed, the pressure was not increased further, and the intake pressure was regarded as the leak-generating intake pressure.
[0191] The test results of the sealing effect are summarized in Table 3 below.
[0192] Sealing effect against air leakage
[0193]
Table 3
[0194]
[0195] It can be seen from the results in Table 3 above that even if the type of substrate sheet is different, the sheet-like tissue bonding reinforcement material ("sheet-like LYDEX") of the present application also exerts roughly the same sealing effect. Compared with the test results of the comparative example implemented previously, a high sealing effect was confirmed compared with the case of directly using a two-reaction formulation in the form of powder for bonding ("LYDEX (powder)"), the case of directly using fibrin paste, and the case of using it together with a mesh sheet.
[0196] <Example 6> Adhesion strength evaluation test
[0197] The adhesive sheet of Example 4-1 ("LYDEX sheet / PLLA mesh density") was used to evaluate the adhesive strength in vitro. The test was conducted with reference to JIS K6850 Adhesives - Rigid Adhesive Materials Tensile Shear Adhesion Strength Test Method, with the test piece and test conditions appropriately changed.
[0198] As a substitute for the imagined organs, the object to be bonded with the adhesive sheet was a longitudinally cut "collagen casing" (cylindrical shape with a thickness of 28 μm and a diameter of 20 mm) produced by Nippi Co., Ltd. Figure 4 As shown in the schematic diagram, the adhesive sheet of Example 4-1 and the "collagen casing" are cut into small pieces of 5×2 cm, and the position from one end to 1.25 cm on one surface of these is set as the bonding part, and marked with a marker. The small piece of the adhesive sheet and the small piece of the "collagen casing" are bonded between the bonding parts. At this time, after spraying 0.2-0.5 mL of physiological saline on the bonding part of the small piece of the "collagen casing", it is overlapped and pressed with the bonding part of the small piece of the adhesive sheet of Example 4-1, thereby pasting. And, after 3 minutes of gelation time (including 30 seconds of compression time), the small piece of the adhesive sheet and the small piece of the "collagen casing" except the bonding part are clamped by the upper and lower chucks of the testing machine respectively. In addition, during the tensile test, the test speed (rising speed of the crosshead) is 50 mm / min, the load range is 10N 1%, and the recording speed is 200 mm / min.
[0199] The specific tensile strength test steps are as follows.
[0200] 1. Wipe the adhesive part and the vicinity of the small piece of "collagen casing" (2.5×5 cm) with a scientific experiment paper wiper (Kimberly-Clark Corporation's "KimWipe S-200") soaked with ethanol and leave it for 30 seconds to dry. Then, mark the boundary between the adhesive part and the other part.
[0201] 2. Spray physiological saline onto the adhesive part of the small pieces of "collagen casing".
[0202] 3. After covering the bonding part with an adhesive sheet (LYDEX sheet) and spraying physiological saline, a weight was placed to apply pressure. The weight used was a weight (weight of about 200 g) obtained by stacking a vial filled with water on a PTFE petri dish (inner diameter 50 mm).
[0203] 4. After 30 seconds of starting to press with the weight, remove the weight. Then, let it stand for another 2 minutes and 30 seconds. Therefore, the total gelation time is 3 minutes.
[0204] 5. After 3 minutes of gelation, install it in a universal testing machine (tensile / compression testing machine) by grasping the vicinity of the marked position with the chuck of the universal testing machine. At this time, grasp the adhesive sheet with the upper chuck and grasp the small piece of collagen casing with the lower chuck.
[0205] 6. Start the test (raise the crosshead at 50 mm / min).
[0206] In addition, as a comparative example, a material formed by bonding a small piece of "collagen casing" and a small piece of mesh sheet ("PLLA mesh density") used in Example 4-1 with a fibrin paste ("Bolheel tissue bonding" of KM Biologics Co., Ltd.) was used. The size of each small piece to be bonded and the size of the bonding portion were the same as those in the example using the above-mentioned adhesive sheet. In addition, the specific tensile strength test procedure at this time was changed only in 2. to 3. of the tensile strength test steps 1. to 6. of the above-mentioned example as follows.
[0207] 2. Use the attached double syringe to apply about 0.3 mL of fibrin paste ("Bolheel Tissue Adhesive") to the adhesive part of the small piece of "Collagen Casing".
[0208] 3. As soon as possible, place the bonding part of the small piece of mesh sheet ("PLLA mesh density") on the coated bonding part, and place the above-mentioned weight (weight: about 200 g) to press.
[0209] The results obtained by the adhesive strength evaluation test are summarized in the following Tables 4 to 5 and Figure 8 middle.
[0210] Adhesive sheet of Example 4-1 ("LYDEX sheet / PLLA mesh density")
[0211]
Table 4
[0212]
[0213] Fibrin paste + "PLLA mesh density"
[0214]
Table 5
[0215]
[0216] It is believed that the bonding strength between the adhesive sheet ("LYDEX sheet / PLLA mesh density") of Example 4-1 and the collagen casing is quite large, which fully meets the purpose of bonding and strengthening biological tissues. After being peeled by stretching, the water-containing gel as the adhesive layer also adheres (remains) on the collagen casing. That is, it is believed that the adhesive layer is destroyed.
[0217] On the other hand, in the case of a mesh sheet using fibrin paste and poly-L-lactic acid (PLLA), after being peeled off by stretching, the hydrogel as the adhesive layer only exists on the mesh sheet side, and no attachment (residue) is found on the surface of the collagen casing. Also, the adhesive layer is not destroyed, but only the surface destruction between the collagen casing is carried out. It is believed that even if the fibrin paste is simply used in combination with a biodegradable mesh sheet, it should not be suitable as an adhesive sheet for bonding biological tissues.
[0218] <Example 7> Preparation of adhesive sheet by spraying powder onto cotton fibrous collagen sheet
[0219] As the base sheet, "Integran" "Pressed Sheet" (100 mm×50 mm, 0.2 g of cotton fibrous collagen) manufactured by Koken Co., Ltd. was used as it is in the same manner as in Example 1.
[0220] The same mixed powder of the two-reactant adhesive ("LYDEX 2.5 / 20") as used in Examples 1 and 4 was used. Fig. 9The powder spraying device (spray gun) shown sprays 1.0 g of the mixed powder of the two-reactant adhesive uniformly onto the entire substrate sheet (5×10 cm). In addition, a small amount (about 5%) of the sprayed mixed powder is scattered and not carried on the substrate sheet. After applying the mixed resin powder, a small sprayer for drug administration is used to spray mist of anhydrous ethanol on the mixed powder. Then, after drying at room temperature overnight, it is placed in a vacuum dryer at room temperature for 6 hours and taken out.
[0221] Before being placed in the dryer and in the dryer, the obtained adhesive sheet is flat to some extent, but when it is taken out of the vacuum state, it absorbs moisture rapidly and warps violently. This state indicates that Fig.10 The upper part of the photo. When the warped adhesive sheet is placed in a drying box, it returns to a flat state. When the adhesive sheet is rolled up in the direction of the long side so that the diameter is about 1 cm, the rolling is completed when ripples and sounds are generated. Fig.11 The photo shows the situation when it is rolled up and then stretched out. Fig.11 As shown, the mixed powder of the two-reactant adhesive is slightly peeled off.
[0222] <Example 8> Addition of Hydroxypropyl Cellulose (HPC)
[0223] By the same experiment as in Example 7, it was examined whether softness or toughness could be imparted to the adhesive resin layer by adding hydroxypropyl cellulose (HPC) when forming an adhesive resin layer including a two-reactive agent type adhesive.
[0224] For this purpose, instead of 1.0 g of a mixed powder of a two-reactant adhesive ("LYDEX 2.5 / 20"), a mixed resin powder obtained by uniformly mixing 0.8 g of the mixed powder and 0.2 g of hydroxypropyl cellulose (HPC) using an ultrasonic stirring device was used. The mixed resin powder was coated on the above-mentioned substrate sheet (5×10 cm). The other conditions and operations for making the adhesive sheet were exactly the same as those in Example 7. The hydroxypropyl cellulose used here was NISSO HPCSSL (D 50 20μm, 2% aqueous solution viscosity 2~2.9mPa·s), based on the pharmacopoeia, it contains 53.4~80.5% of hydroxypropoxy groups (-OC3H6OH: 75.09) relative to the converted dry product.
[0225] The obtained adhesive sheet is shown in Fig.10 In addition, exactly the same as in Example 7-1, Fig.12 The photo shows the situation when it is temporarily rolled into a roll and then unrolled and stretched. Fig.12It can be seen that the mixed powder of the two-reactant adhesive is slightly peeled off. Fig.11 When compared with the results of Example 7-1 shown, it is believed that the addition of hydroxypropyl cellulose (HPC) significantly reduced the falling of the mixed powder of the two-reactant type adhesive. In other words, it is believed that the addition of hydroxypropyl cellulose (HPC) can impart flexibility or toughness to the adhesive resin layer.
[0226] The adhesive sheets obtained in Examples 7 and 8 were cut with scissors and the cross-section was observed with a high-performance stereoscopic microscope ("Digital Microscope VHX-5000" system manufactured by KEYENCE Co., Ltd.), thereby measuring the thickness of the adhesive resin layer. That is, six positions were randomly selected from the screen of the microscope device and the thickness was measured, and the average was calculated. The results are shown in Table 6.
[0227] Thickness of adhesive resin layer
[0228]
Table 6
[0229]
[0230] As shown in Table 6, the adhesive resin layer can be formed to be about 0.30 to 0.35 mm (about 300 to 350 μm). When a coating solution containing 20% hydroxypropyl cellulose (HPC) was used, the number of locations with small thickness decreased and the overall thickness increased slightly.
[0231] <Reference example> Study on the conditions and mechanism of forming the adhesive resin layer
[0232] In the following series of experiments (reference examples 1 to 8), in order to simplify the experiments, as a substitute for the biodegradable substrate sheet, a paper wiper for scientific experiments ("KimWipe S-200" of Nippon Paper Crecia Co., Ltd.) cut into 5×5 cm or 2.5×5 cm (only reference example 3) was used directly. When the thickness of the paper wiper was measured at multiple locations using a micrometer screw gauge, it was about 30 to 70 μm. In addition, the paper wiper ("KimWipe S-200") is composed only of bleached chemical pulp from wood (coniferous trees and broad-leaved trees), and is a strong sheet with little fluff and paper powder, and is subjected to a wrinkle process (texture process). The pulp here is a pulp made by mixing cellulose fibers of 3 to 5 mm in length and about 20 μm in width from coniferous trees and cellulose fibers of 1 to 2 mm in length and about 50 μm in width from broad-leaved trees at a specified ratio.
[0233] <Reference Example 1> Anhydrous ethanol
[0234] 0.5 g of the mixed powder ("LYDEX 2.5 / 20") of the two-reactant adhesive (LYDEX) used in Example 1 etc. was dispersed in 6 mL (4.9 g) of "anhydrous" ethanol (ethanol 99.5 vol% or more, Wako Grade 1) in exactly the same procedure as in Example 1. Then, the dispersion was applied to a sheet of a paper wiper (5×5 cm of "KimWipe S-200") in exactly the same manner and dried.
[0235] The transformation of the mixed powder of the two-reactant type adhesive (Lydex) into a resin layer was observed using a high-performance stereoscopic microscope ("Digital Microscope VHX-5000" system manufactured by KEYENCE Co., Ltd.). Fig.13 The set of photographs shows a series of stages from the preparation of the dispersion to the sheet after the resin layer is formed. Specifically, the following are shown: (1) the dispersion in a dish; (2) the coated sheet immediately after the dispersion is applied to the sheet on a flat surface lined with silicone resin; (3) the coating layer when it begins to dry locally (enlarged photograph); (4) the coating layer overflowing (scattering) next to (near) the substrate sheet, when the coating sheet at the time point of (2) and the drying start portion at the time point of (3) are moved to another dish; (5) the coated sheet after being left at room temperature in the atmosphere for about 1 hour; and (6) the coated sheet when it is completely dried. In addition, after being left to dry for about 1 hour, the coated sheet is transferred to a dark brown thick paper towel ("Kimtowel Four-fold" by Nippon PaperCrecia Co., Ltd.), and these photographs (5) and (6) show the dried coated sheet placed on the thick paper towel.
[0236] In addition, Fig.14 In a set of photos, different magnifications (100x and 400x) are used to show the plane images based on the three-stage microscope. Fig.15 The cross section of the coating sheet after complete drying is shown (100 times).
[0237] Right now, Fig.14 From top to bottom, they represent the following 〔1〕~〔3〕, Fig.15 Indicates the following〔4〕.
[0238] [1] An ethanol-impregnated product obtained by impregnating anhydrous ethanol into a two-reactant adhesive (LYDEX). That is, the coating layer before drying in (2) above was observed on a glass dish as shown in (4) above.
[0239] [2] During coating, the dispersion that overflows (sprinkles) from the sheet is partially dried to obtain a partially dried product. That is, the sheet is peeled off from the flat surface on which it was placed during coating in the above-mentioned (3) and observed.
[0240] [3] The surface of the adhesive resin layer forming sheet of (5) above which has been dried for about 1 hour.
[0241] [4] Cut the cross section of the completely dried adhesive resin layer forming sheet of the above (6) with scissors.
[0242] like Fig.14 〔1〕, especially as shown in the oval-enclosed portion of the right-hand magnified photograph (×400), a portion believed to be soluble in succinic anhydride-modified polylysine (SAPL) was observed. Fig.14 〔2〕, especially the enlarged photo on the right (×400), the powders are bonded together at the local drying locations. Fig.14 〔3〕and Fig.15 ((4)) It can be seen that after drying, the powders of the two-reactant adhesive are bonded to each other, thereby forming an adhesive resin layer. The randomly shaped powders of the aldehyde-modified dextran (AD) in the adhesive resin layer form convex portions and adhere to the paper wipe sheet as the substrate sheet. In addition, according to Fig.15 According to the cross-sectional photograph, the thickness of the paper wipe is 39 μm at the thinnest part and 53 μm at the thickest part.
[0243] <Reference Example 2> Non-aqueous acetone
[0244] In exactly the same procedure as in Example 1 and Reference Example 1, 0.5 g of a mixed powder ("LYDEX 2.5 / 20") of the two-reactant adhesive (LYDEX) used in Example 1 and the like was dispersed in 6 mL (4.9 g) of "anhydrous" ethanol (acetone 99.5 vol% or more, Wako Grade 1). Then, the dispersion was applied to a paper wiper sheet ("KimWipes S-200" 5×5 cm) in exactly the same manner and dried. In addition, the acetone was used immediately after removing the seal of the reagent bottle, and the water content was confirmed to be about 0.2 to 0.3% by Karl Fischer titration (chemical solution for ketones).
[0245] The same operation as in the above-mentioned reference example 1 was performed. Fig.13 A set of photos of the same Fig.16 A set of photos shows the situation at each stage. In addition, Fig.17 Indicates the same as in the above-mentioned reference example 1 Fig.14 A series of microscope photographs obtained in exactly the same manner. However, since no adhesive resin layer was formed, no observation of the cut surface was performed. Then, Fig.18 The left and right groups of photos show the situation when the paper is placed on a dark brown thick paper towel ("Kimtowel Four-fold" produced by Nippon PaperCrecia Co., Ltd.) and observed with a stereo microscope in the same manner as above. Fig.17 The dry powder obtained after a series of operations (left photo), and the mixed powder of the original two-reactant adhesive (LYDEX) (right photo; "LYDEX 2.5 / 20").
[0246] Depend on Fig.17 It can be seen that the mixed powder of the two-reactant adhesive (LYDEX) can be dispersed in acetone, but no local dissolution phenomenon is observed in acetone as in the case of anhydrous ethanol, and fluidity is maintained even at the time of local drying. In other words, the formation of a resin layer caused by the bonding between the powders does not occur. In addition, Fig.18 It is found that even after being dispersed in acetone and dried, no clear change is observed in the shape of the mixed powder of the two-reactant type adhesive (LYDEX).
[0247] <Reference Example 3> 2% aqueous acetone
[0248] Aqueous acetone having a water content of 2% is prepared by adding distilled water to the above-mentioned acetone (Wako Grade 1). Then, using the 2% aqueous acetone as a dispersion medium, the adhesive powder is dispersed in the dispersion medium, applied ("fixed") to the substrate sheet, and dried in the same manner as in the above-mentioned Example 1 and the above-mentioned Reference Examples 1 to 2. However, the size of the paper wipe sheet is set to half, 2.5×5 cm, and the amount of the two-reactant adhesive and the amount of the dispersion medium are also set to half. That is, 0.25 g of the mixed powder ("LYDEX 2.5 / 20") of the two-reactant adhesive (LYDEX) used in Example 1, etc. is dispersed in 3 mL (2.4 g) of 2% aqueous acetone using exactly the same steps as in Example 1. Then, the adhesive sheet obtained after coating and drying is pinched and lifted with tweezers for observation.
[0249] exist Fig.19 This situation is shown in a series of photos. Fig. 20 Representation and Fig.14 The lower end and Fig.17 The right photo is a partial enlargement of the left photo. Fig.19 As shown in the series of photos, especially the photo on the right, when 2% aqueous acetone is used, the adhesive resin can be fixed on the substrate sheet, unlike the case of using non-aqueous acetone (Reference Example 2). That is, a continuous adhesive resin layer can be formed on the substrate sheet. Fig. 20 Photo of the surface with Fig.17 It can be seen from the lower end that the grains are closely attached to each other.
[0250] <Reference Example 4> Non-reactive similar mixed powder
[0251] As a substitute for the aldehyde-modified dextran (first reactant; AD), a powder of the above-mentioned dextran ("Dex-70" of Meito Sangyo Co., Ltd.) used in the raw material was used. Then, the powder of the dextran was mixed with the same powder of succinic anhydride-treated polylysine (second reactant; SAPL) as used in the above-mentioned Example 1 at a weight ratio of 4 / 1. Using the non-reactive similar mixed powder ("Dex-70+SAPL") thus obtained, an adhesive sheet was prepared by the same operation as in the above-mentioned Reference Examples 1 to 2.
[0252] That is, first, 0.5 g of a similar mixed powder ("Dex-70+SAPL") was added to 6 mL (4.9 g) of "anhydrous" ethanol (ethanol 99.5 vol% or more, Wako Grade 1) in the same procedure as in Example 1, and the mixture was uniformly dispersed by ultrasonic stirring. Then, the dispersion was applied to a sheet of a paper wiper (5×5 cm of "KimWipe S-200") in exactly the same manner and dried. Fig.21 As shown in the upper right photograph, the paper wiper sheet can be formed by fixing a resin layer on one side thereof.
[0253] After the dried resin layer molded sheet is cut into three equal parts, it is bent by winding it around the arm. Fig.21 As shown in the right photo of the middle section of the figure, cracks appeared on the resin layer. However, no peeling or detachment was found in the resin layer or the adhesive powder (particles). In this state, physiological saline was sprayed to wet the entire resin layer molding sheet. Fig.21 As shown in the left half of the lower part of the figure, it is attached to the skin surface of the arm. However, of course, no gelation occurs.
[0254] On the other hand, Fig.21 As shown in the right half of the lower section, the above-mentioned non-reactive similar mixed powder ("Dex-70+SAPL") is placed in a culture dish. When water is added, the whole becomes a viscous, uniform and transparent liquid.
[0255] <Reference Example 5> Modification of polylysine only (second reactant; SAPL)
[0256] Only the powder of modified polylysine (succinic anhydride treated polylysine) is used, and a resin molded sheet is prepared by the same operation as Reference Examples 1 to 2. That is, a resin molded sheet is prepared using the same powder of modified polylysine (residual amino group ratio 84.7%) used in the above-mentioned embodiments and reference examples. Specifically, 0.5 g of modified polylysine (SAPL) powder is added to 6 mL (4.9 g) of "anhydrous" ethanol (ethanol 99.5 vol% or more, Wako grade 1) in the same steps as in Example 1, and it is evenly dispersed by ultrasonic stirring. Then, the dispersion is applied to a sheet of paper wiper (5×5 cm of "KimWipe S-200") in exactly the same manner and dried.
[0257] like Fig. 22 As shown in a series of photos in the upper section of the figure, as ethanol as a dispersion medium evaporates from the dispersion applied to the sheet of paper wiper, a colorless and transparent resin layer is formed. After being completely dried, the formed resin layer molding sheet has the appearance of a transparent resin film laminated on the sheet of paper wiper. The resin layer molding sheet thus obtained is cut into less than one-third of the size with scissors and placed on the top plate of a laboratory table composed of melamine decorative panels. Then, by spraying physiological saline, the entirety of the resin layer molding sheet is wetted. Thus, the resin layer molding sheet is attached to the top plate of the laboratory table. However, when it is dried after several hours, it is naturally peeled off from the top plate of the laboratory table.
[0258] According to the results obtained by the above reference example ( Figures 13 to 22 ), think as follows.
[0259] (i) The reason for forming the adhesive resin layer on the porous substrate sheet is that the powder of modified polylysine (SAPL) partially dissolves in anhydrous ethanol or an equivalent dispersion medium.
[0260] (ii) Therefore, in the formation of the adhesive resin layer on the substrate sheet, the reaction between the aldehyde group and the amino group, that is, the reaction for hydrogelation is not required at all.
[0261] (iii) The powder of aldehyde-dextran (AD) itself hardly changes in shape in anhydrous ethanol or an equivalent dispersion medium.
[0262] (iv) The adhesive resin layer on the substrate sheet is considered to be formed by particles (granular portion) derived from the aldehyde-dextran (AD) powder being linked to each other through a continuous layer derived from modified polylysine (SAPL) and fixed on the substrate sheet. In view of the structure of such an adhesive resin layer, it is considered that even if the aldehyde group reacts with the amino group, it is limited to the surface of the particles (granular portion) derived from the aldehyde-dextran (AD) powder.
[0263] (v) The substrate sheet may be a fiber product sheet having a thickness of about 30 to 70 μm. The fiber product sheet may have a porous structure equivalent to that of a paper wiper made of only wood pulp. That is, a fiber product sheet having such a thickness and porous structure can fix and reinforce the adhesive resin layer to a desired degree.
[0264] Industrial Applicability
[0265] The sheet-like tissue reinforcing material of the present invention has a high tissue reinforcing effect and can be used as a hemostatic material for surgical operations and trauma and as an air leakage prevention material for lung resection surfaces, and therefore can be used, for example, in the medical product manufacturing industry.
Claims
1. A sheet-like tissue bonding reinforcement material, characterized in that: include: A substrate sheet having biodegradability and a porous interconnected structure; as well as The adhesive resin layer formed thereon is fixed by ethanol having a water content of 1% or less or acetone having a water content of 1 to 3%, The adhesive resin layer comprises: a first reactant comprising an aldehyde-modified dextran; as well as a second reactant comprising partially carboxylated polylysine, The adhesive resin layer has: the granular structure of the powder from the first reactant; and The second reactant forms a bonding layer that bonds the granular structures to each other and fixes them to the substrate sheet.
2. The sheet-like tissue bonding reinforcement material according to claim 1, characterized in that: The substrate sheet is a non-woven fabric, a woven fabric, a knitted fabric, a mesh sheet, a sponge sheet or other porous interconnected sheets, and has a thickness of 15 μm to 500 μm. The thickness of the adhesive resin layer is 100 μm to 800 μm.
3. The sheet-like tissue bonding reinforcement material according to claim 1 or 2, characterized in that: The average particle size of the granular structure of the powder derived from the first reactant is 20 to 100 μm.
4. The sheet-like tissue bonding reinforcement material according to any one of claims 1 to 3, characterized in that: The amount of aldehyde groups introduced into the aldehyde-modified dextran constituting the first reactant is 0.2 to 0.5 aldehyde groups per monosaccharide unit. The residual amino group ratio of the partially carboxylated polylysine constituting the second reactant is 70 to 93%.
5. The sheet-like tissue bonding and reinforcing material according to any one of claims 1 to 4, characterized in that: The adhesive resin layer contains thrombin, snake venom hemocoagulase or other blood coagulation promoters.
6. The sheet-like tissue bonding and reinforcing material according to any one of claims 1 to 5, characterized in that: Based on the total weight of the first reactant and the second reactant, the adhesive resin layer contains: 5 to 30% by weight of hydroxypropyl cellulose (HPC), hydroxypropyl methyl cellulose (HPMC), collagen or its derivatives, or other biodegradable polymers, and / or 1 to 25% by weight of glycerin or other moisturizing ingredients.
7. A method for manufacturing a sheet-like tissue bonding reinforcement material, characterized in that: Prepare: A substrate sheet having biodegradability and a porous interconnected structure; a powder of a first reactant comprising aldehyde-modified dextran; a powder of a second reactant containing partially carboxylated polylysine; and a dispersion medium of ethanol or an equivalent hydrophilic solvent having a water content of less than 2%, wherein the dispersion medium is capable of dispersing the powders of the first and second reactants, On the substrate sheet, the dispersion medium is allowed to permeate at least into the powder of the second reactant, thereby forming a layer containing the first reactant, the second reactant and the dispersion medium on the substrate sheet, Thereafter, the dispersion medium is removed to form an adhesive resin layer containing the first reactant and the second reactant fixed on the base sheet.
8. The method for manufacturing a sheet-like tissue bonding reinforcement material according to claim 6, characterized in that: Prepare a mixed powder of the first reactant and the second reactant, After forming a layer containing the mixed powder and the dispersion on the substrate sheet by any one of the following (i) to (iv) or any combination thereof, the dispersion medium is removed. (i) preparing a dispersion in which the mixed powder is dispersed in the dispersion medium, and applying the dispersion by spraying the dispersion onto the substrate sheet; (ii) preparing a dispersion in which the mixed powder is dispersed in the dispersion medium, and applying the dispersion by bringing the substrate sheet into contact with a layer obtained by spreading the dispersion on the surface; (iii) after coating the mixed powder on the substrate sheet, coating the dispersion medium, or allowing the dispersion medium to penetrate into the coated substrate sheet; (iv) After the dispersion medium is impregnated into the base sheet, the mixed powder is applied.
9. The method for manufacturing a sheet-like tissue bonding reinforcement material according to claim 7 or 8, characterized in that: When the mixed powder is applied by the method (iii) or (iv), a powder coating device is used, wherein the powder coating device comprises: A powder ejection part that allows the powder to fall from a mesh, a plurality of small holes, or a spray gun or a dispenser; and A driving mechanism that continuously or sequentially moves the relative position of the base sheet to the powder ejection unit.
10. The method for producing a sheet-like tissue bonding reinforcement material according to any one of claims 7 to 9, characterized in that: include: A step of adding hydroxypropyl cellulose (HPC), hydroxypropyl methyl cellulose (HPMC), collagen or its derivatives, or other biodegradable polymers that can be dissolved or dispersed in a dispersion medium, and / or glycerin or other moisturizing ingredients to a dispersion medium or a mixed powder of a first reactant and a second reactant, or to a powder of the first reactant or the second reactant.
11. The method for producing a sheet-like tissue bonding reinforcement material according to any one of claims 7 to 10, characterized in that: include: A step of adding thrombin, snake venom hemocoagulase or other blood coagulation promoter to a dispersion medium or a mixed powder of the first reactant and the second reactant, or to the powder of the first reactant or the second reactant.
Citation Information
Patent Citations
Medical powder spray device
JP2016063919A
Device for measuring remaining thickness of blast furnace stave and method for measuring remaining thickness of blast furnace stave
JP2017222915A
Self-degradable adhesive for medical use of two-component reactant system comprising powder-liquid or powder-powder
WO2008066182A1